At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Let g(x) = 3x, and h(x) = x2 + 1

Let Gx 3x And Hx X2 1 class=

Sagot :

Given:

[tex]\begin{gathered} g(x)=3x \\ \\ h(x)=x^2+1 \end{gathered}[/tex]

Find:

[tex]\begin{gathered} g(-1),\text{ }h(3),\text{ }g(g(-1)),\text{ }h(h(3)),\text{ }g(x)\times h(x),\text{ }g(-2)\times h(-2) \\ \end{gathered}[/tex]

Sol:

(a)

Value of g(-1)

[tex]\begin{gathered} g(x)=3x \\ \\ g(-1)=3\times(-1) \\ \\ g(-1)=-3 \\ \end{gathered}[/tex]

(b)

Value of h(3) is:

[tex]\begin{gathered} h(x)=x^2+1 \\ \\ h(3)=3^2+1 \\ \\ h(3)=9+1 \\ \\ h(3)=10 \end{gathered}[/tex]

(c)

Value of g(g(-1))

[tex]\begin{gathered} g(x)=3x \\ \\ g(g(x)) \\ \text{ } \\ \text{ Then }x=g(x) \\ \\ g(g(x)=3(3x) \\ \\ g(g(x))=9x \end{gathered}[/tex]

So the value of g(g(-1)) is:

[tex]\begin{gathered} g(g(x))=9x \\ \\ g(g(-1))=9(-1) \\ \\ g(g(-1))=-9 \end{gathered}[/tex]

(c)

Value of h(h(3)) is:

[tex]\begin{gathered} h(x)=x^2+1 \\ \\ x=h(x) \\ \\ \text{ Then,} \\ \\ h(h(x))=(x^2+1)^2+1 \\ \\ h(h(x))=x^4+2x^2+2 \\ \\ \end{gathered}[/tex]

So, the value of h(h(3)).

[tex]\begin{gathered} h(h(x))=x^4+2x^2+2 \\ \\ h(h(3))=3^4+2(3)^2+2 \\ \\ =81+18+2 \\ \\ =101 \end{gathered}[/tex]

(d)

Value of g(x)*h(x)

[tex]\begin{gathered} g(x)=3x \\ \\ h(x)=x^2+1 \\ \\ g(x)*h(x)=3x(x^2+1) \\ \\ g(x)^*h(x)=3x^3+3x \end{gathered}[/tex]

(e)

Value of g(-2)*h(-2)

[tex]\begin{gathered} g(x)^*h(x)=3x^3+3x \\ \\ g(-2)^*h(-2)=3(-2)^3+3(-2) \\ \\ =-24-6 \\ \\ =-30 \end{gathered}[/tex]